2009
DOI: 10.1029/2009gl037725
|View full text |Cite
|
Sign up to set email alerts
|

Magnetosheath fluctuations at Venus for two extreme orientations of the interplanetary magnetic field

Abstract: [1] Using the magnetosheath crossings of Venus Express on two consecutive days, we investigate magnetic fluctuations in the same locations for two extreme interplanetary magnetic field orientations, i.e., nearly along and nearly perpendicular to the solar wind flow. It is shown that the properties of the fluctuations are drastically different at basically the same location of the spacecraft in the magnetosheath. The strength and properties of the fluctuations are strongly controlled by the types of the upstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Espley et al (2004) interpret their observed fluctuations as mirror mode waves, but they also admit that this interpretation is in conflict with the observation of a moderate elliptical polarisation of the waves, as theoretical studies suggest that mirror modes are linearly polarised. But they argue that elliptically polarised mirror mode waves have also been observed in Earth's magnetosheath.…”
Section: Wave Properties At Venus and Marsmentioning
confidence: 98%
See 4 more Smart Citations
“…Espley et al (2004) interpret their observed fluctuations as mirror mode waves, but they also admit that this interpretation is in conflict with the observation of a moderate elliptical polarisation of the waves, as theoretical studies suggest that mirror modes are linearly polarised. But they argue that elliptically polarised mirror mode waves have also been observed in Earth's magnetosheath.…”
Section: Wave Properties At Venus and Marsmentioning
confidence: 98%
“…We note that according to Song and Russell (1999) high ratios are favoured, because the propagation direction is better determined for higher ratios of the eigenvalues. Therefore, we use a more stringent condition than Espley et al (2004) and consider only cases with the intermediate to minimum eigenvalue ratio greater than 5. This is a compromise, because otherwise we lose a significant portion of the data set in the analysis.…”
Section: Wave Vector Directionmentioning
confidence: 99%
See 3 more Smart Citations